Assessment of phenotypic and storage protein diversity in exotic barley cultivated in District Dir (Pakistan) - Ali, M.; Nisar, M.; Khan, W.; Naz, T.; Zaman, S. U.; Hussain, M. (Regulatory Mechanisms in Biosystems, 2019)
A total of 198 exotic barley genotypes were collected from the Gene Bank of the Plant Genetic Resource Institute (PGRI), National Agriculture Research Center (NARC), Islamabad, Pakistan, for the assessment of genetic diversity based on morphological and seed storage proteins. Qualitative and quantitative traits were noted as per IPGRI, 1994 descriptor. Among the quantitative parameters, a high level of genetic variability index was noted in seeds per spike at 79.9% of coefficient of variance followed by biomass per plant which shows 37.4% variance, while minimum variance in quantitative traits was noted in days to germination at 5.4% followed by days to maturity at 3.1% with average mean genetic variation in all quantitative traits at 97.6%. Assay of total seed protein in these exotic accessions was analogue through polyacrylamide gel electrophoresis. A high level of variation was noted in loci (bands) B26 (0.98%) followed by B25 (0.89%), B24 (0.78%),B23 (0.69%) and B01 (0.52%). A similarly low level of variation was detected in B03 (0.16%) followed by B06 (0.18%), B13 (0.19%), B12 (0.21%), B11 (0.23%), B05 (0.24%), B07 (0.25%), B21 (0.34%), B20 (0.35%), B17 (0.39%). The results indicate that the mean value of variation in these accessions is 97.6%. Further assessments and exploration were suggested for these genotypes in multi-climatic zones to satisfy farmers’ need, breeders’ interest and malt-industrial requirements.